Analysis of antacid tablets using the alkalimetric titration method - Agung Yulian; Beta Ria Yunita; Desti Nadia; Fadhila Nur Afifah; Faiha Putri Kanza; Febby Trianingsih; Gerend Erlina Ayu Putri (DAS Institute, 2023)
Titrimetry is a quantitative analysis concerned with measuring the volume of a solution of known concentration required to react with the substance to be determined. On the other hand, alkalimetry determines the levels of acidic compounds that are reacted with essential standard solutions. Antacids can treat stomach disorders resulting from excess stomach acid production. The active ingredient is a mixture of magnesium hydroxide and aluminum hydroxide which is a weak base that reacts with acids. This study aims to determine whether the levels of antacid tablets in several pharmacies in Bandar Lampung City by looking at the expiration date meet USP30_NF25 requirements, namely between 90.0% -110% of the amount stated on the label. The method used is alkalimetry with a back titration technique, in which excess acid is added to the sample to react with antacids, and the excess acid is titrated using sodium hydroxide with phenolphthalein solution as an indicator.